2010
DOI: 10.1002/acp.1699
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative fixation: Effects of others' ideas on brainstorming

Abstract: Three experiments examined whether or not fixation effects occur in brainstorming as a function of receiving ideas from others. Exchanging ideas in a group reduced the number of domains of ideas that were explored by participants. Additionally, ideas given by brainstormers conformed to ideas suggested by other participants. Temporal analyses showed how the quantity, variety and novelty of ideas fluctuate over the course of a brainstorming session. Taking a break modulated the natural decline over time in the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
191
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(203 citation statements)
references
References 55 publications
(82 reference statements)
8
191
3
1
Order By: Relevance
“…But the phrases shown were the most likely, thus not novel or creative-and poor examples have been shown to hinder creativity [20,24,32].…”
Section: Discussionmentioning
confidence: 99%
“…But the phrases shown were the most likely, thus not novel or creative-and poor examples have been shown to hinder creativity [20,24,32].…”
Section: Discussionmentioning
confidence: 99%
“…Similar lines of thinking led to a number of learning strategies in educational practices, such as small group teaching and cooperative learning. Subsequently, a number of studies about brainstorming showed that it did not really work; sometimes, brainstorming led to opposite effects, such as idea fixation [136]. However, Seelig, in her popular book inGenius: A Crash Course on Creativity [137], insisted that brainstorming was effective, and she blamed the detractors for not "understanding how different brainstorming is from normal conversation".…”
Section: Discussionmentioning
confidence: 99%
“…For example, while exposure to mundane examples may hinder creativity [19,23], individuals can come up with more diverse and/or creative ideas if they have access to diverse and high quality inspirational examples [6,31,36,44,45,46]. The net effect of increasing individual creativity is that the community can converge on novel, high quality solutions more quickly than if all participants simply saw their own ideas [4].…”
Section: Creativity Enhancing Interventionsmentioning
confidence: 99%